The level of NPQEL participants’ interaction in the e-learning portal and its relationship with the participants’ achievement / Ashfahani Zakaria ... [et al.] - Zakaria, Ashfahani; Sahid, Paridon; Zainuddin, Muhammad Khairiltitov; Zaharin, Siti Suhaini; Besah @ Sitam, Ekhwan (UiTM Press, 2020)
The e-Learning phase encompasses 70% learning hours of the National Professional Qualification for Educational Leaders (NPQEL) course at the Aminuddin Baki Institute (IAB), thus it plays a major role in determining the quality of the course. During the e-Learning phase, the participants of NPQEL course have the opportunity to interact with the contents of the course, other participants, and the lecturers. The objectives of this paper are to identify the level of NPQEL participants’ interaction in the e-Learning portal and to determine the relationship between the level of interaction and the participants’ achievement. The sample of the study consisted of 394 NPQEL participants. The research design used for this study was the Explanatory-Mixed-Method-Design. Data were collected by means of questionnaires, open-ended questions, interviews, and online data analyses. Overall, the results showed that the participants had a high perception on their level of interaction in the e-Learning portal. The results also showed that only the interaction between the participants and the contents had significant relationship with the participants’ achievement. Qualitative data analysis has not only provided clarifications about the situations being studied but also contributed ideas for the improvement of the contents and delivery approach to enhance the quality of the overall interaction in the e-Learning portal.